Profitability, Company Size and Asset Structure on Capital Structure of Food and Beverage Companies in Indonesia Stock Exchange 2019-2021 - Ni Putu Yeni Astiti; Ni Made Indah Mentari; Ni Putu Winda Lestari Putri (Universitas Trisakti, 2023)
Capital structure is a description of the form of the financial proportion of a company, that is, between the capital obtained from debt and the own capital that is the source of the company's financing. The objective of this study is to find out the impact of profitability, size of the Company and asset structure on the capital structure of the food and beverage company in 2019-2021. The population in the study is food and drink companies that are listed on the Indonesian Stock Exchange 2019-2021 as a total of 26 companies. Where samples are selected by purposive sampling. The data analysis technique used in this study is double linear regression. The results of this study show that profitability and asset structure have a negative and significant impact on the capital structure, while the size of the company has a positive and significant effect on capital structure.